Influence of acylpeptide hydrolase polymorphisms on valproic acid level in Chinese epilepsy patients. (July 2016) - Wen, Zhi Peng; Fan, Shuang Shi; Du, Can; Yin, Tao; Zhou, Bo Ting; Peng, Ze Feng; Xie, Yuan Yang; Zhang, Wei; Chen, Yao; Tang, Jie; Xiao, Jian; Chen, Xiao Ping
Background: Concomitant use of meropenem (MEPM) can dramatically decrease valproic acid (VPA) plasma level. It is accepted that inhibition in acylpeptide hydrolase (APEH) activity by MEPM coadministration was the trigger of this drug–drug interaction.Aim: To investigate the influence of APEH genetic polymorphisms on VPA plasma concentration in Chinese epilepsy patients.Patients & methods: Urinary VPA-d6 β-D-glucuronide concentration was determined in 19 patients with VPA treatment alone (n = 10) or concomitant use with MEPM (n = 9). A retrospective study was performed on 149 epilepsy patients to investigate the influence of APEH polymorphisms rs3816877 and rs1131095 on adjusted plasma VPA concentration (CVPA ) at steady-state.Results: Urinary VPA-d6 β-D-glucuronide (VPA-G) concentration was increased significantly in patients with MEPM coadministration. The CVPA of patients carrying the APEH rs3816877 C/C genotype was significantly higher than that of C/T carriers, and the difference was still obvious when stratified by UGT2B7 rs7668258 polymorphism.Conclusion: APEH polymorphism has significant influence on VPA pharmacokinetics in Chinese population.